HPLC and GC–MS–based metabolic profiles and in vivo anticonvulsant, sedative, and antinociceptive potentials of truffles Tirmania nivea and Tirmania pinoyi hydromethanolic extracts in mice. (31st August 2022) - Aboutabl, Mona E.; Elkhateeb, Waill A.; Masoud, Marwa A.; Daba, Ghoson M.; Afifi, Ahmed H.; Hussein, Rehab A.
Abstract: GC–MS and HPLC analyses of the hydromethanolic extracts of the truffles Tirmania nivea (TN) and Tirmania pinoyi (TP) revealed the presence of 18 metabolites and 11 polyphenols, respectively. In vivo, TP extract protected against subcutaneous pentylenetetrazole (scPTZ) and maximal electric shock (MES)‐induced convulsions faster than TN extract. TP extract (100 and 300 mg/kg) showed 100% protection and longer duration than TN extract in the scPTZ test. Similarly, at 300 mg/kg, TP demonstrated a quicker start (75%) and longer duration of action (100%) than TN in MES test. In the scPTZ test, ED50 of TP demonstrated greater anticonvulsant efficacy than that of TN. In mice given TP and TN treatments, the brain GABA levels noticeably increased. TP (100 and 300 mg/kg) produced a notable sedative effect in open‐field test, whereas TN (100 or 300 mg/kg) and TP (300 mg/kg) reduced sleep latency by 52%, 45%, and 79%, respectively. In writhing test, TN (100 or 300 mg/kg) significantly enhanced analgesic efficacy by 50 and 87%, respectively. Comparatively, in formalin test, TP and TN at a dosage of 300 mg/kg decreased the length of the licking by 34 and 59%, respectively. For the first time, this study explains the anticonvulsant, sedative, central, and peripheral analgesic activities of truffle extracts.